Chemical oxidation applications for industrial wastewaters - Tunay, Olcay (IWA Publishing, 2010)
This book covers the most recent scientific and technological developments (state-of-the-art) in the field of chemical oxidation processes applicable for the efficient treatment of biologically-difficult-to-degrade, toxic and/or recalcitrant effluents originating from different manufacturing processes. This book covers the most recent scientific and technological developments (state-of-the-art) in the field of chemical oxidation processes applicable for the efficient treatment of biologically-difficult-to-degrade, toxic and/or recalcitrant effluents originating from different manufacturing processes.
Keywords: Waste products.; Sewage -- Purification -- Oxidation.; elektronické knihy; electronic books